The deficit myth modern monetary theory and how to build a better economy - Kelton,Stephanie (London John Murray, 2020)
Supporting the economy, paying for healthcare, creating new jobs, preventing a climate apocalypse: how can we pay for it all? Leading economic thinker Stephanie Kelton, shows how misguided that question is, and how a radical new approach can maximise our potential as a society. Everything that we've been led to believe about deficits and the role of money and government spending is wrong. Rather than asking the self-defeating question of how to pay for the crucial improvements our society needs, Kelton guides us to ask: which deficits actually matter?
Includes index
Keywords: Money